2014
DOI: 10.7448/ias.17.4.19617
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of causes of death among HIV‐infected patients of Kiev Regional AIDS Center during 2013

Abstract: Ukraine is a leader in Europe in the prevalence of HIV infection. There are up to 270 thousand people, who are living with HIV. Since 1987, in Ukraine, 33,149 HIV-infected people died. During the first six months of 2013, of all the dead, who were suffering from HIV and in need of antiretroviral treatment (ART) at the time of death, 41% received treatment and only 5.7% received ART for more than one year. Specialists of Kiev Regional AIDS Center analyzed mortality among the patients of the centre, in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…28 Data from Kiev showed that in the first six months of 2013, only 41% of persons who died from HIV/AIDS-related causes had received HIV treatment and only 5.7% of those who died had received ART for more than one year. 40 Although the number of PWID receiving ART increased from 2006 to 2011, coverage among this population remains very low. 30 …”
Section: Country Case Studiesmentioning
confidence: 99%
“…28 Data from Kiev showed that in the first six months of 2013, only 41% of persons who died from HIV/AIDS-related causes had received HIV treatment and only 5.7% of those who died had received ART for more than one year. 40 Although the number of PWID receiving ART increased from 2006 to 2011, coverage among this population remains very low. 30 …”
Section: Country Case Studiesmentioning
confidence: 99%
“…Although the decline in HIV prevalence occurred during a period of increasing coverage of harm reduction and OAT, there are several possible alternative explanations of the decreasing prevalence. First, the mortality rate among people living with HIV is very high in Ukraine especially among PWIDs due to high prevalence of HIV and tuberculosis comorbidity among this population [54][55][56]. Second, older HIV-infected PWIDs could have stopped injecting drugs once they were diagnosed with HIV, thus being ineligible for the survey.…”
Section: Discussionmentioning
confidence: 99%